Le droit international privé dans l’espace européen dénationalisé - Mari, Luigi (Studi Urbinati, A - Scienze giuridiche, politiche ed economiche, 2015)
The European Union has long pursued a full program of unification of the national rules on private international law. For the theoretical advantages of uniformity, created by “denazionalizing” the systematic of civil law, corresponds, howewer, a loss of meaning in terms of culture and legal values, at the expense of the identities and the political choices, that only in the national communities – in the absence of democratic processes at the European level – can still find ways of legitimate expression. Paper presented at the Conference “La dimension culturelle du droit international privé (Journée en l’honneur de Tito Ballarino)”, held on June 13, 2014 in Losanna, at the Swiss Institute of Comparative Law. L’Unione europea persegue da tempo un nutrito programma di uniformazione delle normative nazionali di diritto internazionale privato. Ai vantaggi teorici dell’uniformità, artificialmente creata denazionalizzando la sistematica del diritto civile, corrisponde tuttavia una perdita di senso in termini di cultura e di valori giuridici, a scapito delle identità e delle scelte politiche che solo nelle comunità nazionali – in assenza di processi autenticamente democratici a livello europeo – possono ancora trovare legittima espressione. Relazione presentata al Convegno “La dimension culturelle du droit international privé (Journée en l’honneur de Tito Ballarino)”, tenutosi il 13 giugno 2014 a Losanna, presso l’Istituto svizzero di diritto comparato